THE IMPACT OF TECHNOLOGY ON STUDENT LEARNING IN THE CLASSROOM - Mahkamova Robiya; Karimova Jamila (Western European Studies, 2024)
The quality of education is closely tied to socio-economic factors, including the increasing use of technology in production, the growth of the educational services market, and the widespread adoption of information technologies (IT). Today, IT is not only a teaching tool but also a subject of study across all educational levels. While modern IT offers many advantages over traditional teaching methods, there are also negative aspects that affect educational quality. A recent sociological study among vocational and schoolchildren found that 82% own internet-connected cell phones and use them during classes, with about one-third staying online for more than 20 minutes and over one-fourth for more than 45 minutes.
Keywords: education; information technologies